New, additional and historical records of Leptophlebiidae (Insecta, Ephemeroptera) from Colombia - Lopez,Jhon Faber Marulanda (2020)
Abstract In the Neotropical region, especially South America, Leptophlebiidae achieves its higher diversity, with 45 genera and almost 250 species. In Colombia, the diversity about this family is underestimated, with only 22 species reported so far. In order to contribute to the current knowledge of the Leptophlebiidae in Colombia we examined the adults of this family deposited at the Colección Entomológica del Programa de Biología, Universidad de Caldas. In addition to the historical records herein presented, nine species are registered for the first time from the country (Farrodes savagei, F. tepui, F. xingu, Hagenulopsis minuta, Terpides contamanensis, T. echinovaris, T. ornatodermis, Tikuna atramentum, and Ulmeritoides flavopedes). Besides that, additional records are presented for 12 species of the following genera: Askola, Farrodes, Simothraulopsis, Tikuna, Ulmeritoides, Hydrosmilodon, Terpides, Choroterpes, Paramaka, and Hagenulopsis. With these additional and new records, we update the list of Leptophlebiidae from Colombia to 33 species and 14 genera.